1998
DOI: 10.1209/epl/i1998-00417-3
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced orientations in a lyotropic defective lamellar phase

Abstract: The influence of shear on a defective lamellar phase of the ternary mixture sodium dodecyl sulphate/decanol/D2O was studied using small-angle neutron scattering (SANS), smallangle light scattering (SALS) and birefringence. Shear flow leads to an alignment of lamellae but in addition to previous studies, we found a reorientation from "perpendicular" lamellae, i.e. with the layer normal along the vorticity direction, to "parallel" lamellae with the layer normal along the velocity gradient direction at increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 20 publications
5
60
1
Order By: Relevance
“…In fact, many different shear effects have been reported: transformation from lamellar phases to Multi-lamellar vesicles, MLVs (or ''onions''), in different amphiphilic systems and followed by different techniques [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; formation of MLVs in presence of submicron-size particles (''stuffed onions'') [21]; changes in lamellar orientation [17,22,23]; formation of intermediates with cylindrical structure between a lamellar and MLV phases [24][25][26]; reduction in lamellar spacing [27]; transitions from MLVs to unilamellar vesicles [28] and ''layering'' effects on onions [8,29]. As a practical application, these MLVs can be used, for instance, to encapsulate chemicals leading to a new kind of controlled micro-reactor [30] or as carriers for oligonucleotide delivery [31].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many different shear effects have been reported: transformation from lamellar phases to Multi-lamellar vesicles, MLVs (or ''onions''), in different amphiphilic systems and followed by different techniques [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; formation of MLVs in presence of submicron-size particles (''stuffed onions'') [21]; changes in lamellar orientation [17,22,23]; formation of intermediates with cylindrical structure between a lamellar and MLV phases [24][25][26]; reduction in lamellar spacing [27]; transitions from MLVs to unilamellar vesicles [28] and ''layering'' effects on onions [8,29]. As a practical application, these MLVs can be used, for instance, to encapsulate chemicals leading to a new kind of controlled micro-reactor [30] or as carriers for oligonucleotide delivery [31].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of flow on lyotropic lamellar phases have been recently widely studied [1][2][3][4][5][6][7]. It has been shown that under shear some rearrangements of the lamellae occur which lead to well-defined steady-state orientations.…”
Section: Introductionmentioning
confidence: 99%
“…To design functional materials, one must understand the physical basis of the effects of molecular architecture and processing conditions (especially shear frequency, strain and temperature) on the rheological response of the liquid crystalline mesophases (Berghausen et al 1998;Rey & Denn 2002). The distribution of defects within a liquid crystal domain, defined as the 'texture' of the liquid crystal, plays a significant role in its rheology (Rey & Denn 2002).…”
Section: Large-scale Lb Simulations Of Liquid Crystalline Rheologymentioning
confidence: 99%